CHARACTER ASSOCIATION AND PATH ANALYSIS IN GARLIC (ALLIUM SATIVUM L.) - V. RAKESH SHARMA; KOMOLAFE OMOTAYO; SUNIL MALIK; MUKESH KUMAR; ANIL SIROHI (The Bioscan, 2016)
An experiment was conducted using one hundred and thirty-one genotypes of garlic for identifying the characters which mainly contributed to the bulb weight per plant with correlation and path analysis using twelve morpho agronomic characters. The character association analysis revealed the bulb weight per plant showed positive significant correlation with plant height (0.541, 0.508), leaf length (0.461, 0.419), pseudostem height (0.430, 0.417), pseudostem diameter (0.562, 0.509), polar diameter of bulb (0.733, 0.714), equatorial diameter of bulb (0.858, 0.827), number of cloves per bulb (0.322, 0.317), clove length (0.581, 0.545) and clove weight (0.713, 0.706) at both genotypic and phenotype levels, respectively. The maximum direct effect with significant positive correlation were showed by equatorial diameter of bulb (0.828), polar diameter of bulb (0.714), clove weight (0.706), length of clove (0.545) and pseudostem diameter (0.510). The characters like equatorial diameter of bulb, clove weight, number of cloves per bulb shows that they are the most important bulb weight determinants, because of their high direct and indirect effects via many other yield improving characters. The study indicated that these characters can be used as key traits for improving the bulb weight of garlic. Keywords Garlic, Allium sativum, Correlation, Path analysis, Bulb weight.